Strategi Komunikasi Pemasaran PT. Allianz Life Indonesia Dalam Pengambilan Keputusan Nasabah - Adisty Adisty; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This article contains the correspondence system of PT. Allianz Life Indonesia in the client's independent direction focuses on the means of creating an appropriate exchange, specifically distinguishing interest groups, selecting correspondence targets, planning messages, deciding on media, selecting message beginnings, gathering input, selecting complete progress rules, selecting mixed progress, and choose an ad mix strategy. The exploration strategy is a subjective story strategy using information checking methods such as Interactive Matthew B. Miles and A. Michael Huberman. Due to exploration, the depiction shows that the correspondence technique displays PT. Allianz focuses on 2-way correspondence for clients to sell their goods so that they can provide effects, beliefs and activities that are taken as direct input. good use.